Islam and the development of democratic opposition in central Asia - Akhmetova, Elmira (International Institute of Advanced Islamic Studies Malaysia, 2018)
This article provides a brief study of democracy in the five Central Asian countries, i.e. Kyrgyzstan, Kazakhstan, Uzbekistan, Tajikistan and Turkmenistan. It suggests that the expected democratisation of Central Asia failed to occur due to the region’s internal conditions, which can be termed the ‘classic colonial syndrome’, in addition to several international factors. The Central Asian countries did not have the potential to find their own way in the international arena, simply maintaining their traditional Soviet way of rule under the new name of ‘democracy’. The paper also finds that the Central Asian approach to Islam at both state and individual level is a crucial tool of identity construction as well as an instrument of authority, control and suppression of political opposition. Yet, Islam played almost no role in the failure of democracy in the region. This article states that the application of instruments of democracy alone cannot make nations democratic or provide well-being and justice for the people. Democracy is about sets of values and principles aimed at achieving good governance. Thus, democracy should be considered as a tool and structure on the path of achieving societal well-being, rather than as the main objective of governance.